AB0941 NEURALGIC AMYOTROPHY AND HEPATITIS E INFECTION: REPORT OF 6 CASES AND REVIEW OF THE LITERATURE. (2nd June 2020) - Garofoli, R.; Seror, P.; Zauderer, J.; Nguyen, C.; Rannou, F.; Drapé, J. L.; Roren, A.; Lefevre Colau, M. M.
Abstract : Background: Neuralgic amyotrophy (NA) or Parsonage and Turner syndrome is triggered at least in 25% by a viral infection: parvovirus B19, CMV, HSV, etc... Recently, few cases of Hepatitis E Virus (HEV) related NA were reported. This particular association remains little known and is overlooked by most physicians. Besides, clinical, electrodiagnostic (EDX) and MRI characteristics, as well as evolution of HEV-related NA have not been fully described yet. Objectives: To describe 6 cases of HEV-related NA and to perform a review of the literature. Methods: We describe longitudinally clinical examination, electrodiagnostic (EDX), biological and MRI results of 6 cases of HEV-associated NA, diagnosed in our center. Results: The 6 cases were aged between 33 and 57 years old (mean 44.5), sex ratio was 5M/1F. All patients had positive IgM anti-HEV (serology) and a cervical MRI that could not explain clinical presentation. Overall, the 6 patients totalize 26 mononeuropathies (range 1 to 8 per patient), 5/6 patients had a severe presentation of NA, with bilateral and asymmetric symptoms (3 cases). HEV-related NA involved classical nerves such as supra-scapular (6 cases, twice bilaterally) and long thoracic nerves (5 cases), some less classical nerves like anterior interosseous nerve (3 cases, twice bilaterally), and some very unusual ones such as the lateral antebrachial cutaneous nerve (1 case) and the sensory fibers of median nerve (1 case). NA also involved accessory spinal (2 cases, once bilaterally) and phrenic nerves (1 case bilaterally), both originating from cervical plexus. The EDX pattern of these nerve lesions consisted of unique or multiple extensive asymmetric inflammatory mononeuropathies with severe axonal loss and numerous denervation signs damage involving mostly the supra-scapular. On scapular MRI (available for 5/6 patients), amyotrophy in at least one muscle was observed in all patients. Out of 26 nerves involved, after 12 months all had well recovered (above 3/5 MRC scale). Conclusion: HEV should be systematically screened when NA is suspected, whatever the severity, if the onset is less than 3 or 4 months (before IgMs anti-HEV disappear). HEV-related NA appears to be frequently associated with a severe pattern, without modifying the recovery usually observed. Disclosure of Interests: Romain Garofoli: None declared, Paul Seror: None declared, Jennifer Zauderer: None declared, Christelle Nguyen: None declared, François Rannou Grant/research support from: Pierre Fabre, Fidia, MSD, Pfizer, Bone Therapeutics, Expanscience, Grunenthal, Thuasne, Genévrier, Fondation Arthritis, Consultant of: Pierre Fabre, Fidia, MSD, Pfizer, Bone Therapeutics, Expanscience, Grunenthal, Thuasne, Genévrier, Speakers bureau: Pierre Fabre, Fidia, MSD, Pfizer, Bone Therapeutics, Expanscience, Grunenthal, Thuasne, Jean-Luc Drapé: None declared, Alexandra Roren: None declared, Marie-Martine Lefevre Colau: None declared